Analysing indoor mycobiomes through a large‐scale citizen science study in Norway. Issue 11 (7th May 2021) - Martin‐Sanchez, Pedro M.; Estensmo, Eva‐Lena F.; Morgado, Luis N.; Maurice, Sundy; Engh, Ingeborg B.; Skrede, Inger; Kauserud, Håvard
Abstract: In the built environment, fungi can cause important deterioration of building materials and have adverse health effects on occupants. Increased knowledge about indoor mycobiomes from different regions of the world, and their main environmental determinants, will enable improved indoor air quality management and identification of health risks. This is the first citizen science study of indoor mycobiomes at a large geographical scale in Europe, including 271 houses from Norway and 807 dust samples from three house compartments: outside of the building, living room and bathroom. The fungal community composition determined by DNA metabarcoding was clearly different between indoor and outdoor samples, but there were no significant differences between the two indoor compartments. The 32 selected variables, related to the outdoor environment, building features and occupant characteristics, accounted for 15% of the overall variation in community composition, with the house compartment as the key factor (7.6%). Next, climate was the main driver of the dust mycobiomes (4.2%), while building and occupant variables had significant but minor influences (1.4% and 1.1%, respectively). The house‐dust mycobiomes were dominated by ascomycetes (⁓70%) with Capnodiales and Eurotiales as the most abundant orders. Compared to the outdoor samples, the indoor mycobiomes showed higher species richness, which is probably due to the mixture of fungi from outdoor and indoor sources. The main indoor indicator fungi belonged to two ecological groups with allergenic potential: xerophilic moulds and skin‐associated yeasts. Our results suggest that citizen science is a successful approach for unravelling the built microbiome at large geographical scales.